Synthesis and Characterization of Coconut Pith Char Adsorbents for Carbon Dioxide Capture - Kuanasealan, Keshveeni (Universiti Teknologi PETRONAS, 2016)
The purpose of this study is to investigate the performance of coconut pith char as an adsorbent for capturing anthropogenic CO2 gas before it is emitted to the atmosphere. Coconut pith chars were successfully synthesized and characterized as a potential CO2 adsorbent. Coconut pith char was used for carbonization process at various temperatures (300ºC-700ºC). The char adsorbents obtained were characterized using Yield and Proximate analysis, Nitrogen adsorption-desorption analysis (NAD), CHNS elemental analysis, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The porous properties of the coconut pith chars obtained including the Brunauer-Emmett Teller (BET) surface area, pore volume and average pore diameter were determined by nitrogen adsorption isotherms. The results obtained showed that with increase in carbonization temperature, changes of physical and chemical properties of the char adsorbent were observed. The highest BET surface area was noticed in CP700 with an area of 315.06 m2 /g, pore diameter of 1.9 nm and pore volume of 149.70 (cm3/g) x103 . However, CP500 the highest adsorption capacity of about 1.1 mmole/g. From the obtained results, it is feasible to produce coconut pith chars with high CO2 adsorption capacity by selecting the appropriate conditions for carbonization.